QUALITY IMPROVEMENT OF SEISMIC IMAGE FROM 2D PSDM (PRE STACK DEPTH MIGRATION) USING TOMOGRAPHY FOR INTERVAL VELOCITY MODEL REFINEMENT - Hagayudha Timotius; Yulinar Firdaus (BULLETIN OF THE MARINE GEOLOGY, 2013)
The main goal of seismic exploration is to get an accurate image of subsurface section so it can be easily interpreted. Pre Stack Depth Migration (PSDM) is such a powerful imaging tool especially for complex area such an area where strong lateral velocity variations exist. The main challenge of PSDM is the need of accurate interval velocity model.In this research, Dix Transformation, coherency inversion, and tomography are used for initial interval velocity model, and then tomography is used for interval velocity model refinement. We compare also between seismic image resulted from PSDM and PSTM to determine the best method. The seismic data that processed in this paper is derived from north western part of Australian Waters. Kata kunci: Pre Stack Depth Migration, Dix Transformation, coherency inversion, tomography. Tujuan utama dari eksplorasi seismik adalah menghasilkan citra yang akurat dari penampang bawah permukaan sehingga diinterpretasi lebih mudah. Pre Stack Depth Migration (PSDM) merupakan suatu metode yang memberikan hasil peningkatan kualitas citra seismik pada daerah kompleks dimana terjadi variasi kecepatan lateral yang signifikan. Salah satu syarat penting yang harus dipenuhi agar hasil PSDM lebih optimal adalah model kecepatan interval yang akurat. Dalam penelitian ini Transformasi Dix, inversi koheren, dan tomografi digunakan untuk memenuhi syarat tersebut. Perbandingan hasil penampang seimik PSDM dan PSTM dilakukan untuk menentukan metode terbaik. Data seismik yang diolah dalam tulisan ini berasal dari wilayah Perairan Baratlaut Australia. Kata kunci: Pre Stack Depth Migration, Transformasi Dix, inversi koheren, tomografi